The Land Legal Politics in Creating the Prosperity of Indonesian Society - Tiromsi Sitanggang; Sumarno Sumarno (Jurnal Akta, 2022)
Land is a necessity that is needed by citizens, in the current era, it is inseparable from various kinds of interests that result in the occurrence of land politics. The purpose of this paper is to find out and analyze the politics of land law to create people's prosperity. The approach method uses a normative juridical approach. The results of the writing can be concluded that the politics of land law in creating people's prosperity is carried out by laying the foundations for the preparation of the National Agrarian Law, which will be a tool to bring prosperity, happiness, and justice to the state and people, especially the people. In the context of a just and prosperous society and the implementation of land law politics in creating people's prosperity, it is regulated that the distribution of land rights that can be granted can be distinguished as regulated in Article 16 paragraph (1) of the Basic Agrarian Law.